2020
DOI: 10.1186/s13000-019-0922-1
|View full text |Cite
|
Sign up to set email alerts
|

Orbital involvement by NUT midline carcinoma: new presentation and encouraging outcome managed by radiotherapy combined with tyrosine kinase inhibitor: a case report

Abstract: Background: NUT midline carcinoma (NMC) is a poorly differentiated squamous cancer with a median survival at less than 7 months. NMC is resistant to conventional chemotherapies and characterized by rearrangement of the NUT gene. Case presentation: Here, we described a patient who initially presented with epiphora, and an orbit involved NMC. In addition, we for the first time demonstrated that local radiotherapy combined with tyrosine kinase inhibitor (TKI) could significantly inhibit tumor progression in orbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In addition, two patients with orbital NUT carcinoma, who had undergone operation, received anlotinib in third-line. The OS was beyond 15 months and 8 months, respectively ( 103 , 104 ).…”
Section: Targeting the Tumor Microenvironmentmentioning
confidence: 99%
“…In addition, two patients with orbital NUT carcinoma, who had undergone operation, received anlotinib in third-line. The OS was beyond 15 months and 8 months, respectively ( 103 , 104 ).…”
Section: Targeting the Tumor Microenvironmentmentioning
confidence: 99%
“…A study by Wang et al indicated that stereotactic radiosurgery (SRS) combined with anlotinib limited brain metastases with perilesional edema in NSCLC [ 20 ]. A recent study has reported that radiotherapy combined with anlotinib to treat with orbital NMC [ 21 ]. In this report, we for the first time used palliative radiotherapy combined with anlotinib could significantly alleviate primary lesion of NMC progression, which may provide a way to treat primary pulmonary NMC.…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al have suggested that combination therapy with anlotinib and chemoradiotherapy may be an effective regimen for the treatment of advanced esophageal squamous cell carcinoma (ESCC) [16]. A study by Wang et al indicated that stereotactic radiosurgery (SRS) combined with anlotinib limited brain metastases with perilesional edema in NSCLC [17]. A recent study has reported that radiotherapy combined with anlotinib to treat with orbital NMC [18].…”
Section: Discussionmentioning
confidence: 99%